2017
DOI: 10.1021/acs.jafc.6b05357
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Characterization of Oxidative Changes in Roasted Almonds Undergoing Accelerated Shelf Life

Abstract: In almonds, there is no standard method for detecting oxidative changes and little data correlating consumer perception with chemical markers of rancidity. To address this, we measured peroxide values (PV), free fatty acid values (FFAs), conjugated dienes, tocopherols, headspace volatiles, and consumer hedonic response in light roasted (LR) and dark roasted (DR) almonds stored under conditions that promote rancidity development over 12 months. Results demonstrate that, although rancidity develops at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 44 publications
9
86
0
Order By: Relevance
“…The relationship between fertilization status of hatching eggs and their VOCs was evaluated using multivariate analysis, such as O‐PLS, PCA, PLS, S‐PLS and cluster analysis. Multivariate analyses could present the distinction among UF, F, and IF eggs and indicate the relative importance of VOCs in explaining the variance of fertilization attributes . It was very clear that the VOCs from UF and Fd eggs were completely separated from each other in all multivariate models and there was an obvious separation trend of VOCs among UF, F, and IF eggs (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The relationship between fertilization status of hatching eggs and their VOCs was evaluated using multivariate analysis, such as O‐PLS, PCA, PLS, S‐PLS and cluster analysis. Multivariate analyses could present the distinction among UF, F, and IF eggs and indicate the relative importance of VOCs in explaining the variance of fertilization attributes . It was very clear that the VOCs from UF and Fd eggs were completely separated from each other in all multivariate models and there was an obvious separation trend of VOCs among UF, F, and IF eggs (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…But it could not identify odor compounds as precisely as gas chromatography‐mass spectrometry (GC‐MS). Solid‐phase microextraction (SPME), which combines sampling, analyte isolation, enrichment, and clean‐up into one step, is a versatile, effective, and easily automated assay for VOC sample preparation . Gas chromatography‐mass spectrometry has been widely used to identify VOCs in food materials by advanced library searches …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almonds have been the largest specialty crop export in the United States (USDA, 2013). During storage, the physical and chemical quality of almonds will degrade and eventually result in consumer rejection (Franklin et al, 2017). Current industry practices include storing raw almonds in unlined cardboard cartons (UC), and roasted almonds either in polypropylene bags (PPB) or high barrier bags (HBB) (ABC, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Almond kernels have a compartmentalised microstructure that protects against oxidation, and evidence has shown this protective microstructure can be disrupted by roasting (Perren & Escher, 2013). A recent study investigated light roasted and dark roasted almonds and found that although peroxides proliferated at a greater rate in dark roasted almonds, consumer liking was not significantly different between light and dark roasted almonds (Franklin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%